Understanding biosecurity behaviors of Australian beef cattle farmers using the ten basic human values framework - Fountain, Jake; Manyweathers, Jennifer; Brookes, Victoria J.; Hernandez-Jover, Marta (Frontiers in Veterinary Science, 2023)
On-farm biosecurity is an essential component of successful disease management in the beef cattle industry on an individual, regional, and national level. Participation in mandatory or voluntary assurance schemes, knowledge and trusted relationships have all been demonstrated to contribute to the development of behaviors that promote biosecurity. However, compliance with rules, socio-psychological relationships and knowledge-seeking behavior are all contingent upon the motivations and beliefs of the individual. It is widely accepted that the motivations and beliefs of all cultures can be defined by ten basic values (Self-direction, Stimulation, Hedonism, Achievement, Power, Security, Conformity, Tradition, Benevolence and Universalism). In this study, we use the ten basic values to characterize the on-farm biosecurity behaviors of Australian beef farmers to facilitate the identification of interventions that are most likely to align with producer motivations and therefore, more likely to result in wider adoption of effective on-farm biosecurity. Semi-structured interviews were conducted with 11 Australian beef farmers to discuss the reasons behind decisions to alter or implement biosecurity practices in response to endemic diseases. Thematic analysis was used to identify the motivations, opportunities, and capability of biosecurity behaviors. The ten basic human values were used to characterize these behaviors and inform enablers and barriers to biosecurity adoption. Benevolence and Self-direction, relating to self-transcendence and an openness to change, were the principal values associated with good biosecurity behaviors. This suggests that farmers will be receptive to education strategies that communicate the actual risk of disease in their area, the impact of disease on animal welfare, and the ability for on-farm biosecurity to mitigate these impacts. Farmers also expressed values of Security which entrenched behaviors as common practice; however, in some cases the Security of trusted relationships was identified as a potential barrier to behavior change. Overall, values associated with biosecurity behaviors were found to align with values that are most important for social cohesion, suggesting that collaborative disease efforts between industry stakeholders and farmers are likely to succeed if designed with these values in mind.